uaTHE POETICS OF LOVE POETRY IN ANTHOLOGY OF VASYL MAKHNO “PAPER BRIDGE” (2017) - Pliushchyk, Oksana (Літературний процес: методологія, імена, тенденції, 2019)
DOI: 10.28925/2412-2475.2019.1412 “Paper Bridge” (2017) is the twelfth book of the poems written by Vasyl Makhno (by its nature the collection represents a specific lyrical novel in the form of novelette-poems), being composed of two chapters. The article makes a research of the anthology imagery system combined with the shape of poetic texts, in particular, the author’s distinctness is presented through the expression of the feelings of love. The motif of love in the book is analysed under several aspects: by the means of urban environment, the dramatic art and the style of phrasing (as defined solely by the poet). Most notably, the urban motifs in the life and creative work of the artist are depicted in critical reviews, memories, surveys, interviews, ets. The familiar images from the earlier anthologies appeared also in “Paper Bridge”: bookish and poetic foxes and dogs, ouzels, music, rain, the four seasons, etc. The poetry of Vasyl Makhno always has a Muse — her importance for the author is read nearly through all his poems. His art of painting by means of words portrays the canvas, which sometimes vividly detalizes the erotic and poetic imagination of the belamour image. The image of the sweetheart in authors interpretation is metaphorized and gains poetic style. The anthology “Paper Bridge” is filled with images, created “helically” (the author, getting back to the previous images, either remains them unchanged or transforms them, by reshaping); extends the urban space, makes deeper the image of the beloved person or Muse through erotic motifs; fills the texts with autumn and winter motifs and enriches them with metaphor.